FRI0334 PERFORMANCE OF THE SCLERODERMA SKIN PATIENT-REPORTED OUTCOME (SSPRO) IN A PHASE 2 TRIAL WITH LENABASUM. (June 2019) - Man, Ada; Dgetluck, Nancy; Conley, Brian; White, Barbara
Abstract : Background: Skin thickening is a distressing feature of systemic sclerosis (SSc). The severity and extensiveness of skin thickening, as traditionally assessed by mRSS, may not directly correlate with its effect on patients' health related quality of life (HRQoL). The Scleroderma Skin Patient-reported Outcome (SSPRO) was specifically developed to assess the skin-related HRQoL in SSc. No skin-specific PRO in SSc has been prospectively validated in a clinical trial. Objectives: Validate the SSPRO prospectively in a clinical trial. Methods: The SSPRO, Patient Global Assessment (PtGA), Physician Global Assessment (MDGA), HAQ-DI, mRSS, FVC% predicted, PROMIS-29 questionnaire, and ACR CRISS were assessed prospectively in a Phase 2 study of lenabasum in dcSSc. SSPRO has 18 items that assess four SSc skin-related HRQoL domains. The Phase 2 study of lenabasum had a 4-month double-blinded portion (N = 41 completers) followed by an open-label extension (N = 38 entered). Spearman correlations of baseline values and change values were determined for SSPRO and other outcome measures. Mean change in SSPRO scores were determined in subjects with increasing levels of improvement in other efficacy outcomes. Results: At baseline, SSPRO correlated moderately with all other outcome measures except for FVC%, as expected, with strongest correlations with PtGA, HAQ-DI, and PROMIS-29 pain interference and social role domains (Table 1 ). The mean change in SSPRO scores at 3 and 12 months correlated mostly moderately (r = 0.25 to 0.62) with the mean change in other outcome scores, but correlations were low or inconsistent with mRSS, FVC%, and PROMIS-29 anxiety domain (Table 1 ). Significance of correlations in some outcomes was hampered by small magnitudes of change. Mean SSPRO generally increased in subjects with increasing levels of improvement in HAQ-DI, PtGA, mRSS, and ACR CRISS, although less consistently with mRSS and ACR CRISS at 3 months (Table 2 ). Conclusion: SSPRO score correlates with both physician and patient-reported outcomes at baseline, though correlations with the latter were stronger. Change in SSPRO reflects changes in how the patient feels (PtGA, PROMIS-29 pain interference and depression domains) and functions (HAQ-DI, PROMI-29 physical function and social role domains) and less consistently with physician-assessed outcomes. Subjects with improvement ≥ MID levels of –0.250 in HAQ-DI, -1 in PtGA, and –5 in mRSS had SSPRO improvements of -22 to -23 points at 12 months. Disclosure of Interests: Ada Man Consultant for: Advisory Board Fee: Abbvie, Janssen, Boeringer Ingelheim, Nancy Dgetluck Employee of: Corbus Pharmaceuticals, Inc., Brian Conley Employee of: Corbus Pharmaceuticals, Inc., Barbara White Shareholder of: Corbus Pharmaceuticals, Inc., Employee of: Corbus Pharmaceuticals, Inc.